Taxing the Cloud (International Journal of Engineering and Computer Science, 2017)
Nowadays consumers are more liking to download a software file from the internet then to purchase it from the market.Due to which we can see that the sales of the computer softwares CDs are declining at a very fast rate. Consumers are downloading software files and storing them in cloud, so the government is looking towards the "cloud". As they think that it can be new source for Tax revenues. Today the sales of the USB drive is declining as consumers are preferring to store data in the cloud, which in turn caused decrement in the sales tax revenue as the sale of the physical goods have decreased, but as the government is looking forward to tax the cloud there are many questions that is arising for the taxing of the cloud.In order to impose a tax, the government must have some jurisdiction over the entity they are taxing